METHODOLOGICAL APPROACH TO ASSESSING THE USE OF RESOURCE EFFICIENCY OF THE UNITED TERRITORIAL COMMUNITIES (INNOVATIVE ECONOMY, 2019)
Misiuk M.V., Betz B.B. METHODOLOGICAL APPROACH TO ASSESSING THE USE OF RESOURCE EFFICIENCY OF THE UNITED TERRITORIAL COMMUNITIESPurpose. The purpose of the study is to develop methodological approaches to assess the resource potential of the UTC (United Territorial Community), which take into account the effects, in particular, economic, social and environmental effects that are generated by each type of resource.Methodology of research. General scientific methods are used in the course of the research, in particular: methods of theoretical generalization – to study the theoretical bases of the efficiency of the development of the UTC, the efficiency of the use of resources; coefficient method, which is used in calculating the system of coefficients and their analysis is carried out both in statistics and in dynamics; benchmarking to determine the use of resource efficiency in different UTCs; the principal component method for reducing the number of indicators that determine the overall efficiency of the use of the UTC resources.Findings. The toolkit for the development of united territorial communities should be based on the results of the assessment and analysis of their current state, efficiency of functioning and tendency of changes of the basic indicators of resource efficiency and efficiency of activity. These parameters depend on the resources provided by the UTC. Therefore, this study is based on a causal relationship between the available UTC resources and its effectiveness. The primary focus of the study is on assessing the effectiveness of its resource provision, which involves assessing the resource potential and comparing the potential effects of its use with what has actually been achieved.The development of a methodology for assessing the resource potential of an UTC should be carried out in several stages, the first of which is the determination of indicators, which are quantitative measures (indicators) of each individual type of resources. The list of indicators of the status of a resource base must comply with three principles, namely: 1) the principle of completeness (all resources and their quantitative and qualitative resources should be taken into account); 2) the principle of simplicity (involves elimination of repetition of indicators); 3) the principle of conformity of indicators of reality of the state of information support.Originality. The scientific novelty of the research results is to identify methodological approaches to assessing the resource efficiency of the United Territorial Communities as a means of ensuring the effectiveness of community development.Practical value. Modern approaches to assessing the level of resource provision and resource potential of economic entities have made it possible to distinguish three methodological approaches: 1) determining the effectiveness of the use of resources involved in the functioning of entities; 2) comparative analysis of performance indicators; 3) integrated performance evaluation, which involves the calculation and analysis of a synthetic generalized efficiency factor. These approaches make it possible to carry out a comprehensive analysis of the efficient utilization of the resource potential of the UTC.Key words: methodological approach, efficiency, development, resources, integrated territorial communities.
Keywords: Key words; methodological approach; efficiency; development; resources; integrated territorial communities.